Using World Café to enhance Relationship-building for the Purpose of Developing Trust in Emotional Intelligence Training Environments - Ramsey PL; Gill L; Leberman S; Atkins S (Academic Publishing Ltd, 2016)
Every conversation or action between people involves an element of trust, particularly in workplace training environments. Personal development relies on the quality of trust relationships between trainer and learners, and between learners who experience feelings of vulnerability when dealing with issues that impact self-esteem and individual identity. Responsibility is placed on the trainer to create an environment characterised by trust so that learners feel safe, and unrestricted to embrace personal change, address challenging situations, and reflect on behaviours. Developing such an environment requires attentiveness to effective qualitative methodology. The research aim was to explore the need for relationship-building methodology such as World Café for encouraging the development of trusting relationships. The World Café followed an earlier study of 21 Emotional Intelligence (EI) trainers in New Zealand which sought to identify what variables contribute to the design of successful EI training. World Café was utilised as a relationship-building methodology for further exploring the nature of trust and for evaluating the method. This paper begins with a summary of literature on the nature of trust, then presents themes based on participants’ perspectives. Trust was firstly viewed through the lens of ‘inputs’. While offering a useful perspective, viewing trust as an output offered a practical way for training across different learning environments, organisational contexts, and differences between learners. These findings informed a new practice-based definition of trust. We also present our findings that support the need for relationshipbuilding methods, such as World Café, for building trust during the process of EI training.
Keywords: World Cafe; Relationship building methodology; trust; emotional intelligence; 1503 Business and Management